RELASI KEPEMIMPINAN SITUASIONAL DAN POLA KOMUNIKASI TERHADAP KINERJA TIM PROJECT BISNIS GENERASI Y - Yuli Kartika Dewi; Carolina Mustikarini; Metta Padmalia; Deandra Vidyanata (Nusantara Hasana Journal, 2022)
Entrepreneurship and business have become the main colors in the tertiary curriculum in the last 10 years. The government through BEKRAF and ministerial regulations on graduate standards encourage a curriculum that increases the number of young entrepreneurs in Indonesia. Students who are currently being forged to become young Indonesian entrepreneurs are the millennial generation who have their own character. The amount of information circulating, the rapid development of technology and life in an era of high individuality, make this generation have weaknesses in leading their groups, low ability to communicate effectively, lack of resilience to accept failure and ability to work in teams. This is what causes the lack of performance results and the low sustainability of the business that is being pioneered. This research was conducted to find out how the type of situational leadership and communication patterns in the group can affect the performance of members of the millennial business group. The method used in this research is quantitative by distributing 285 questionnaires to student business startups that have been established for more than 3 months and have a monthly turnover. The results showed that situational leadership and communication patterns had a significant influence on group performance.